2012 IEEE/IFIP 20th International Conference on VLSI and System-on-Chip (VLSI-SoC) 2012
DOI: 10.1109/vlsi-soc.2012.7332094
|View full text |Cite
|
Sign up to set email alerts
|

TamaRISC-CS: An ultra-low-power application-specific processor for compressed sensing

Abstract: Abstract-Compressed sensing (CS) is a universal technique for the compression of sparse signals. CS has been widely used in sensing platforms where portable, autonomous devices have to operate for long periods of time with limited energy resources. Therefore, an ultra-low-power (ULP) CS implementation is vital for these kind of energy-limited systems. Sub-threshold (sub-VT) operation is commonly used for ULP computing, and can also be combined with CS. However, most established CS implementations can achieve e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…• Data compression algorithm : We considered the Compress sensing (CS) algorithm [4], a 50% lossy compression algorithm used on biosignals before storing them. This application takes as input, a 3 seconds Electrocardiogram (ECG) signal and compresses it.…”
Section: Application Characterization and Simulation Methodologymentioning
confidence: 99%
“…• Data compression algorithm : We considered the Compress sensing (CS) algorithm [4], a 50% lossy compression algorithm used on biosignals before storing them. This application takes as input, a 3 seconds Electrocardiogram (ECG) signal and compresses it.…”
Section: Application Characterization and Simulation Methodologymentioning
confidence: 99%
“…The maximum frequency of a 4T GC is also slightly lower than that of a 3T GC because the 4T consumes larger areas, resulting in longer RBLs and, consequently, a longer read access time (RAT). 3T GC and 2T GC have approximately 20% and 35% less area than 4T GC, respectively [9].…”
Section: Proposed Cellmentioning
confidence: 98%
“…1 -layout of 45 nm Intel core i7 processor [7] Furthermore, embedded memories are one of the main consumers of power in most VLSI SoCs [8]. For instance, the power consumption of embedded memories for an ultra-low-power specific processor called TamaRISC-CS was found to be ranging from 70% to 95% of the total power [9]. In addition to this, it was found that the total dynamic and static power consumed by chips for motionless applications is up to 100w [6], while it was stated by ITRS in 2009 that for portable applications the total power consumption for the VLSI SoC processors should not exceed 0.5w or 2w for consumer processors as tablets.…”
mentioning
confidence: 99%
“…These expected area savings should also translate to potential energy savings from driving smaller bit-lines and wordlines. Furthermore, the static power consumption due to leakage has been estimated to contribute to more than 60% of the total power consumption in modern CMOS SRAM arrays [24], [25]. We, therefore, expect significant energy savings courtesy of the SOTFET's nonvolatility.…”
Section: B Comparison To Cmos Alternativesmentioning
confidence: 99%